Pengaruh Harga Saham, Return Saham, dan Pelatihan Pasar Modal terhadap Minat Investasi - Dhimas Fitrian Haryanto; Edi Wibowo (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the influence of stock prices, stock returns, and capital market training on interest in investing in shares in the capital market among students at the Faculty of Economics, Slamet Riyadi Surakarta University. The population of this research were students from the Faculty of Economics, Slamet Riyadi Surakarta University, from whom a sample of 95 respondents was taken using a purposive sampling method with the criteria being that students had/are currently taking capital markets courses. The analytical methods for this research are descriptive analysis, multiple linear regression analysis, t test, F test (model accuracy test), and coefficient of determination test. The results of the research prove that stock prices, stock returns and capital market training partially have a positive and significant effect on interest in investing in shares in the capital market among students at the Faculty of Economics, Slamet Riyadi Surakarta University.